It-which-must-not-be-named: COVID-19 misinformation, tactics to profit from it and to evade content moderation on YouTube - Tokojima Machado, Dayane Fumiyo; Fioravante de Siqueira, Alexandre; Rallo Shimizu, Natiely; Gitahy, Leda (Frontiers in Communication, 2022)
Covid-19 misinformation became accessible and profitable through social media platforms, such as YouTube. Here we investigate if Brazilian YouTube channels previously identified as vaccine misinformation spreaders would also misinform their audience about Covid-19. Our analysis sample consists of six months of content (3,318 videos) from 50 Brazilian YouTube channels. We establish a protocol to classify the types of Covid-19 misinformation spread by the content creators, describing how the channels evade content moderation — disguising, replicating, and dispersing misinformation — and what tactics the content creators use to profit. Our analysis shows that these channels exploited Covid-19 misinformation to promote themselves, profiting in the process.